2021
DOI: 10.3390/ma14040990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Variation of SiC Reinforcement on Wear Behaviour of AZ91 Alloy Composites

Abstract: In this investigation, the extensive wear behaviour of materials was studied using SiC reinforced magnesium alloy composites fabricated through the stir casting process. The wear properties of AZ91 alloy composites with a small variation (i.e., 3%, 6%, 9% and 12%) of SiC particulates were evaluated by varying the normal load with sliding velocity and sliding distance. The worn surfaces were examined by scanning electron microscope to predict the different wear mechanisms on the pin while sliding on the hard di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…This is due to the presence of embedded hard ceramic particles in the soft matrix. A similar observation on wear behaviours was also reported by Kumar et al [ 20 , 26 ]. The wear rate is proportional to the normal load and sliding velocity.…”
Section: Resultssupporting
confidence: 88%
“…This is due to the presence of embedded hard ceramic particles in the soft matrix. A similar observation on wear behaviours was also reported by Kumar et al [ 20 , 26 ]. The wear rate is proportional to the normal load and sliding velocity.…”
Section: Resultssupporting
confidence: 88%
“…It was also observed that the friction coefficient increased with an increase in load from 10 N to 20 N (while maintaining a constant velocity of 1 m/s). However, the friction coefficient decreased when the load was further increased to 30 N. This may be attributed to the increased brittleness of the samples [ 5 ]. The wear rate prominently increased with higher loading, and this observation was for all loading ( Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…The wear rate prominently increased with higher loading, and this observation was for all loading ( Figure 8 ). The wear resistance gets transformed from abrasion to adhesion, reducing the average friction coefficient [ 5 ]. The wear rate of composites increased with the increase in load.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations